2006
DOI: 10.1590/s0101-20612006000300035
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da vida-de-prateleira de fruta estruturada e desidratada obtida de polpa concentrada de mamão

Abstract: RESUMOA fruta estruturada contendo polpa concentrada de mamão (700 g/kg), sacarose (340 g/kg), alginato de sódio (7 g/kg), pectina de baixa metoxilação (7 g/kg) e glicerol (50 g/kg), cortada no formato cilindro sólido (vol. aprox. 2 cm 3 ), desidratada (12% umidade), com cobertura de açúcar impalpável, foi utilizada no estudo de vida-de-prateleira. Foram realizadas análises físicas, químicas, sensoriais e microbiológicas no produto devidamente acondicionado em sacos de filme multilaminado, para acompanhar a ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
4
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 4 publications
3
4
0
5
Order By: Relevance
“…The results found in this work are consistent with the requirements of the fruit market of the "Solo" group, which is of the order of 11.5 °Brix (Fagundes & Yamanishi, 2001). Martins et al (2006) and Grizotto, Berbari, Moura and Claus (2006), observed that SS values should be 11.5 to 11.6 °Brix in the fruit pulp, being this dependent on the maturation stage at which the fruit is harvested (M. I. F. Chitarra & A. B. Chitarra, 2005).…”
Section: Resultssupporting
confidence: 89%
“…The results found in this work are consistent with the requirements of the fruit market of the "Solo" group, which is of the order of 11.5 °Brix (Fagundes & Yamanishi, 2001). Martins et al (2006) and Grizotto, Berbari, Moura and Claus (2006), observed that SS values should be 11.5 to 11.6 °Brix in the fruit pulp, being this dependent on the maturation stage at which the fruit is harvested (M. I. F. Chitarra & A. B. Chitarra, 2005).…”
Section: Resultssupporting
confidence: 89%
“…That is, color change was less accelerated with increased temperature. Similar results were obtained by Ferreira et al (1999), for color degradation in water soluble annatto solution (23.9 kcal.mol -1 ), and Grizotto et al (2006), for the overall quality of fruit made from papaya (19.89 kcal.mol -1 ). Moura et al (2001) found values for activation energy of 8.0 kcal.mol q10 -1 and of 1.55 for instrumental color of strawberry pulp.…”
Section: Quantitative Descriptive Analysissupporting
confidence: 81%
“…O conceito de alimento estruturado ou "designed food" ou "engineered food" refere-se a alimentos que são delineados de acordo com um planejamento, geralmente empregando-se matérias-primas de baixo custo, oriundas de frutas que se encontram fora de classificação para comercialização in natura ou excedentes de produção durante o período de safra, ou mesmo subprodutos de outras indústrias como, por exemplo, recortes de carnes, frango ou pescado, proteínas animais ou vegetais, em muitos casos, utilizando-se hidrocoloides (FIZMAN, 1992;GRIZOTTO et al, 2006).…”
unclassified